1971
DOI: 10.1128/aem.21.5.888-892.1971
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to d-Cycloserine in the Tubercle Bacilli: Mutation Rate and Transport of Alanine in Parental Cells and Drug-Resistant Mutants

Abstract: A single transport system was found to accumulate Land D-alanine, glycine and D-serine in Mycobacterium tuberculosis. The results of inhibition experiments suggested that the antibiotics D-cycloserine and 0-carbamyl-D-serine were also transported by the alanine-glycine-D-serine system. A D-cycloserine-resistant permease-competent (D-CSr/perm+) mutant and a D-cycloserine-resistant permeasedefective (D_CSr/perm-) mutant were isolated. The D_CSr/permmutant was not found to be more resistant to the drug than was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
1

Year Published

1975
1975
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 4 publications
3
10
1
Order By: Relevance
“…Using this approach, we calculated an ultra-low rate of emergence of spontaneous mutations conferring DCS resistance in M. tuberculosis (in the order of 10 −11 mutations per bacterium per cell division, Table 1), and that DCS does not induce mutagenesis. This result is in agreement with the only other report of the mutation rates of DCS with M. tuberculosis 33 . This ultra-low rate of emergence of DCS-resistance mutations is consistent with DCS engaging two lethal targets in M. tuberculosis , Alr and Ddl, and represents an important barrier for the selection of resistance.…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…Using this approach, we calculated an ultra-low rate of emergence of spontaneous mutations conferring DCS resistance in M. tuberculosis (in the order of 10 −11 mutations per bacterium per cell division, Table 1), and that DCS does not induce mutagenesis. This result is in agreement with the only other report of the mutation rates of DCS with M. tuberculosis 33 . This ultra-low rate of emergence of DCS-resistance mutations is consistent with DCS engaging two lethal targets in M. tuberculosis , Alr and Ddl, and represents an important barrier for the selection of resistance.…”
Section: Resultssupporting
confidence: 94%
“…10 −11 ) (ref. 33 and this work). Mutation rate is important, but identifying and understanding potential routes for compensating fitness costs associated with resistance are equally important to evaluate and predict resistance appearance and dynamics in populations 44 .…”
Section: Discussionsupporting
confidence: 64%
“…Fluctuation analysis indicates that the frequency of spontaneous mutations conferring DCS resistance in M. tuberculosis is ultra-low (10 -11 ). This result is in agreement with the only other report of the mutation rate of DCS with M. tuberculosis (29). This ultra-low frequency is consistent with DCS engaging two lethal targets in M. tuberculosis, Alr and Ddl, and represents an important barrier for the selection of resistance.…”
Section: Main Textsupporting
confidence: 93%
“…Evidence suggested that L-homoserine was transported by the former system only. L-Homoserine was found to be a strong competitive inhibitor of both the DAG and LIV transport systems in marine pseudomonad B-16. Systems similar to the alanine-glycine-Dserine-D-cycloserine transport system of E. coli have also been reported in Bacillus megaterium (26), B. subtilis (5), Streptococcus challis (31), and Mycobacterium tuberculosis (9). The system described in B. megaterium also appears to transport AIB.…”
Section: Vol 124 1975mentioning
confidence: 74%